1996
DOI: 10.1111/j.1472-8206.1996.tb00596.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone therapy in elderly people: an age‐delaying drug?

Abstract: The aims of this review are to present a brief overview of growth hormone (GH) physiology and to summarize the studies of GH treatment in adults. Special attention has been paid to randomized controlled trials. Studies have revealed a partial deficiency of GH secretion in the elderly. GH secretion on the average declines by 14% with each decade in normal adults after 20 years of age. Aging has a central effect on the GH secretion and peripheric effect on insulin-like growth factor 1 (IGF-1) through changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 156 publications
(72 reference statements)
0
13
0
Order By: Relevance
“…The use of recombinant human GH is beneficial in the treatment of GH-deficient children [71] and has been shown to reverse some of effects of ageing in the elderly [72]. The GH releasing mechanism was found to be mediated through a G-protein coupled receptor named growth hormone secretagogue receptor type 1 a (GHS-R1a) [73].…”
Section: Growth Hormone Receptor Agonistic Activitymentioning
confidence: 99%
“…The use of recombinant human GH is beneficial in the treatment of GH-deficient children [71] and has been shown to reverse some of effects of ageing in the elderly [72]. The GH releasing mechanism was found to be mediated through a G-protein coupled receptor named growth hormone secretagogue receptor type 1 a (GHS-R1a) [73].…”
Section: Growth Hormone Receptor Agonistic Activitymentioning
confidence: 99%
“…Binding of the hormone to the receptor induces receptor tyrosine phosphorylation with intracellular signaling through a number of pathways, such as signal transducer and activator of transcription 5 (STAT5), Mitogen-activated protein kinase (MAPK), Phosphoinositide-3 kinase (PI3K) and Janus kinase 2 (JAK2) [10], [11], leading to differential gene expression and changes in physiological response. While the role of GH in metabolism has been studied in a number of animal models and in humans undergoing GH therapy [12][16], the contribution of individual pathways to metabolism remains unclear. Treatment of GH-deficient adults or the elderly has been shown to normalize the altered body composition seen in GH deficiency, including increased fat mass, decreased muscle mass and decreased bone mineral density.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed a reduction in plasma concentrations of total testosterone (TT; Drafta et al 1982;Gray et al 1991;Tsitouras and Bulat 1995), dehydroepiandrosterone sulfate (DHEAS; Baulieu 1996;Orentreich et al 1992), growth hormone (GH), and insulin-like growth factor I (IGF-1; Bouillanne et al 1996;Corpas et al 1993;NystroÈ m et al 1997;Rudman et al 1981) have been reported in elderly men. However, the interindividual variations in the reported concentrations of these hormones are considerable (Lamberts et al 1997).…”
Section: Introductionmentioning
confidence: 99%